Children with mild hyponatremia at the emergency department are at higher risk of hospitalization - Stefano Pintaldi; Alessandro Zago; Carlo Pizzolon; Elena Magni; Giorgio Cozzi; Stefanny Andrade; Egidio Barbi; Alessandro Amaddeo (BMC, 2023)
Abstract Background Mild hyponatremia is frequently encountered in the pediatric emergency department (PED). Although usually of little clinical concern, its prognostic meaning as a possible marker of more severe disease has not yet been well established. Methods We retrospectively analyzed data from children and adolescents who performed a blood sample with plasmatic sodium measurement on admission to the PED of IRCCS "Burlo Garofolo" Pediatric Hospital in Trieste, Italy, in 2019. We compared the rate, length of admissions and laboratory characteristics of patients with hyponatremia to those with normal sodium. Results Among 807 subjects, hyponatremia (sodium < 135 mEq/L) was present in 17.6%, being mild (between 130 and 134 mEq/L) in 16.5%. Hyponatremic patients were younger, more frequently males, with an infection diagnosis, mainly of the respiratory tract and viral aetiology. They presented higher C-reactive protein (CRP) levels and erythrocyte sedimentation rates (ESR). Compared to normonatremic individuals, hyponatremic patients presented a higher risk of underlying infection (aOR 2.02; 95%CI 1.33-3.08), hospital admission (aOR 1.72; 95%CI 1.06-2.48), and a hospital stay of > 5 days (aOR 1.99; 95%CI 1.03-3.85). When considering only subjects with mild hyponatremia, we found similar results. Conclusion Hyponatremia and mild hyponatremia in the PED are associated with an increased admission rate and extended hospital stays. Mild hyponatremia should be considered a warning sign for a possibly more serious condition.